2018
DOI: 10.1177/0961203318793215
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of diffusion tensor imaging and cognition in systemic lupus erythematosus

Abstract: Objective This pilot study aimed to examine longitudinal changes in brain structure and function in patients with systemic lupus erythematosus (SLE) using diffusion tensor imaging (DTI) and neuropsychological testing. Methods Fifteen female SLE patients with no history of major neuropsychiatric (NP) manifestations had brain magnetic resonance imaging (MRI) with DTI at baseline and approximately 1.5 years later. At the same time points, a standardized battery of cognitive tests yielding a global cognitive impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
1
18
1
Order By: Relevance
“…Low fractional anisotropy (FA) indicates damaged white matter, which may be due to decreased axonal density, number, diameter or myelination [29]. Decreased FA in the external capsule has been reported in SLE patients with CD [106][107][108]. MTI quantifies the exchange of magnetization between macromolecule-bound proteins in myelin and water protons in biological tissues by generation of a magnetization transfer ratio (MTR).…”
Section: Diffusion Tensor Imaging and Magnetization Transfer Imagingmentioning
confidence: 99%
“…Low fractional anisotropy (FA) indicates damaged white matter, which may be due to decreased axonal density, number, diameter or myelination [29]. Decreased FA in the external capsule has been reported in SLE patients with CD [106][107][108]. MTI quantifies the exchange of magnetization between macromolecule-bound proteins in myelin and water protons in biological tissues by generation of a magnetization transfer ratio (MTR).…”
Section: Diffusion Tensor Imaging and Magnetization Transfer Imagingmentioning
confidence: 99%
“…Thus, there remains a need for an objective and non-invasive means to establish neurological dysfunction in SLE patients both for investigative purposes, as well as for clinical diagnosis and surveillance. There is evidence to suggest that SLE patients, with and without overt NPSLE, have aberrations in their white matter microstructures as seen by diffusion tensor imaging (DTI) [36]. Functional MRI studies have shown increased functional connectivity in core resting-state networks in SLE patients that correlate with reduced cognitive performance compared with healthy controls [37].…”
Section: Advanced Imaging Studiesmentioning
confidence: 99%
“… 35 , 63 In diffusion tensor imaging (DTI) studies of SLE patients, decreased fractional anisotropy (FA) in both PreCG and PoCG was found. 64 Furthermore, we found the significantly negative correlations between glucocorticoid dose and dReHo values in PreCG and left PoCG. These findings suggested the low-sustained dose of glucocorticoid may also contribute to the compensatory mechanism of the left PoCG and right PreCG in non-NPSLE patients.…”
Section: Discussionmentioning
confidence: 55%